En helt underbar titel - Corpus - Hogen, Peter; Namn, Ett; Namn2, Ett; En Institution, Uppsala University (Swedish National Data Service, 2025)
Far far away, behind the word mountains, far from the countries Vokalia and Consonantia, there live the blind texts. Separated they live in Bookmarksgrove right at the coast of the Semantics, a large language ocean. A small river named Duden flows by their place and supplies it with the necessary regelialia. It is a paradisematic country, in which roasted parts of sentences fly into your mouth. Even the all-powerful Pointing has no control about the blind texts it is an almost unorthographic life One day however a small line of blind text by the name of Lorem Ipsum decided to leave for the far World of Grammar. The Big Oxmox advised her not to do so, because there were thousands of bad Commas, wild Question Marks and devious Semikoli, but the Little Blind Text didn’t listen. She packed her seven versalia, put her initial into the belt and made herself on the way. When she reached the first hills of the Italic Mountains, she had a last view back on the skyline of her hometown Bookmarksgrove, the headline of Alphabet Village and the subline of her own road, the Line Lane. Pityful a rethoric question ran over her cheek, then

Långt långt borta, bakom ordet berg, långt från länderna Vokalia och Consonantia, bor de blinda texterna. Separerade bor de i Bookmarksgrove precis vid kusten av Semantics, ett stort språkhav. En liten flod som heter Duden rinner vid deras plats och förser den med nödvändiga regelialia. Det är ett paradisiskt land, där rostade delar av meningar flyger in i munnen. Även den allsmäktige Pointing har ingen kontroll över de blinda texterna, det är ett nästan oortografiskt liv. En dag bestämde sig dock en liten rad blindtexter vid namn Lorem Ipsum för att ge sig av till grammatikens bortre värld. The Big Oxmox rådde henne att inte göra det, eftersom det fanns tusentals dåliga kommatecken, vilda frågetecken och slug Semikoli, men den lilla blinda texten lyssnade inte. Hon packade sina sju versalia, satte sin initial i bältet och gjorde sig själv på vägen. När hon nådde de första kullarna i Italic Mountains, hade hon en sista vy tillbaka på silhuetten av sin hemstad Bookmarksgrove, rubriken till Alphabet Village och underlinjen av hennes egen väg, Line Lane. Det var synd att en retorisk fråga gick över hennes kind
En helt underbar titel - Corpus
Detta är en underbar alternativ titel!
Keywords: managers; chefer; men; män; Human health and safety; Människors hälsa och säkerhet; men's health; mäns hälsa; Woman; Qvinna; DEMOGRAPHY (POPULATION, VITAL STATISTICS, AND CENSUSES); DEMOGRAFI (POPULATION, VITALSTATISTIK OCH FOLKRÄKNINGAR); Migration; Migration; Mathematical Sciences; Matematik; Mathematical Analysis; Matematisk analys; Geometry; Geometri; Algebra and Logic; Algebra och logik; Biota; Biologi och ekologi; Structure; Byggnader och byggnadsanläggningar; Health; Hälsa